PENGUJIAN VIABILITAS Trichogramma spp. (Hymenoptera: Trichogrammatida PADA BEBERAPA TINGKATAN SUHU DAN LAMA WAKTU PENYIMPANAN DI LABORATORIUM - Poibe Tinata Sitorus; Syahrial Oemry; Fatimah Zahara (Universitas Sumatera Utara, 2012)
ABSTRACT The viability test of Trichogramma spp. (Hymenoptera: Trichogrammatidae) on some of the temperature level and depository time depth in the laboratory. Trichogramma spp. is egg parasit from lined stem borer pest (Chilo saccahariphagus) and shining stem borer pest (Chilo auricilius) which is the major pest of sugarcane. The aim of this research is to know the viability of Trichogramma spp. on some of the temperature level and depository time depth in the laboratory. This research used the Complete Randomized Design (CRD) 2 factorial with 12 treatments and 3 replications, T (Temperature) (10oC, 15oC, 20oC,), control (27oC) H (day) (2 days, 4 days, 6 days). The result of this research show that the long time of starter imago appearance found on T0H1 dan T0H2 (27o; 2,4 days) treatment for 0.71 hours and the latest found on T1H1 (10oC, 2 days) treatment for 4.17 hours. The fastest process of parasitic found in T0 (27oC) treatment for 0.71 days and the latest found in T2 (15oC, 2 days) treatment for 2.38 days. The highest presentation of the parasitic found T1H3 (10oC, 6 days) treatment of 97.33% and the lowest found in T0H1, T0 H2, T0 H3 (27oC, 2, 4, 6 days) for 0.71%. The highest total of the imago appearance in a line found in (T1H3 (10oC, 6 days), 35.59 imagoes, and the lowest found in T0H1, T0 H2, T0 H3 (27oC, 2, 4, 6 days) treatment for 0.71 imagoes. Keywords: viability of Trichogramma spp., temperature, depository time depth. ABSTRAK Pengujian viabilitas Trichogramma spp. (hymenoptera: trichogrammatidae) pada beberapa tingkatan suhu dan lama waktu penyimpanan di laboratorium. Parasitoid Trichogramma spp. merupakan parasitoid telur dari hama penggerek batang bergaris (Chilo saccahariphagus) dan penggerek batang berkilat (Chilo auricilius) pada tanaman tebu. Penelitian ini bertujuan untuk mengetahui viabilitas Trichogramma spp. pada beberapa tingkatan suhu dan lama waktu penyimpanan di Laboratorium. Penelitian ini menggunakan Rancangan Acak lengkap (RAL) 2 faktorial dengan 12 perlakuan dengan tiga ulangan yaitu T (suhu) (10oC, 15oC, 20oC), kontrol (27oC) H (hari) (2 hari,4 hari, 6 hari). Hasil penelitian menunjukkan lama waktu munculnya imago starter terdapat pada perlakuan T0H1 dan T0H2 (27oC; 2, 4 hari) yaitu 0.71 jam dan yang paling lama pada perlakuan T1H1 (10oC, 2 hari) yaitu 4.17 jam. Lama proses parasitasi yang paling cepat terdapat pada T0 (27oC) 0.71 hari dan yang paling lama pada T2 (15oC) yaitu 2.38 hari. Persentase parasitasi yang paling tinggi terdapat pada T1H3 (10oC, 6 hari) yaitu 97.33%, dan yang paling rendah pada T0H1, T0 H2, T0 H3 (27oC, 2, 4, 6 hari) yaitu 0.71%. Jumlah imago yang muncul per pias yang tertinggi terdapat pada perlakuan (T1H3 (10oC, 6 hari) yaitu 35.59 ekor, dan yang terendah pada perlakuan T0H1, T0 H2, T0 H3 (27oC, 2, 4, 6 hari) yaitu 0.71 ekor. Kata kunci: viabilitas Trichogramma spp., suhu, lama waktuABSTRACT The viability test of Trichogramma spp. (Hymenoptera: Trichogrammatidae) on some of the temperature level and depository time depth in the laboratory. Trichogramma spp. is egg parasit from lined stem borer pest (Chilo saccahariphagus) and shining stem borer pest (Chilo auricilius) which is the major pest of sugarcane. The aim of this research is to know the viability of Trichogramma spp. on some of the temperature level and depository time depth in the laboratory. This research used the Complete Randomized Design (CRD) 2 factorial with 12 treatments and 3 replications, T (Temperature) (10oC, 15oC, 20oC,), control (27oC) H (day) (2 days, 4 days, 6 days). The result of this research show that the long time of starter imago appearance found on T0H1 dan T0H2 (27o; 2,4 days) treatment for 0.71 hours and the latest found on T1H1 (10oC, 2 days) treatment for 4.17 hours. The fastest process of parasitic found in T0 (27oC) treatment for 0.71 days and the latest found in T2 (15oC, 2 days) treatment for 2.38 days. The highest presentation of the parasitic found T1H3 (10oC, 6 days) treatment of 97.33% and the lowest found in T0H1, T0 H2, T0 H3 (27oC, 2, 4, 6 days) for 0.71%. The highest total of the imago appearance in a line found in (T1H3 (10oC, 6 days), 35.59 imagoes, and the lowest found in T0H1, T0 H2, T0 H3 (27oC, 2, 4, 6 days) treatment for 0.71 imagoes. Keywords: viability of Trichogramma spp., temperature, depository time depth.